Faulty Breast Feeding Practice : A Risk Factor in Malnourished Children - Sen, Sukhendu Shekhar; Sharma, Jhulan Das; Das, Dhananjoy; Iqbal, Shahed; Badruddoza, Md (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2015)
Background: The predominant form of malnutrition is commonly called proteincalorie malnutrition. Protein Energy Malnutrition (PEM) is still a major health problem in children of developing countries including Bangladesh. The causes of malnutrition are multifactorial including nutritional factors, socioeconomic factors, health status of the mothers and repeated infections in children. Objective: To explore the information regarding the breast feeding practices of children suffering from Protein-Energy Malnutrition. Methods: This case control study was conducted in Chittagong Medical College Hospital from November 2006 to April 2007. A total of 65 controls and 65 cases were selected consecutively for the purpose of the study. Their mothers were interviewed with help of structured questionnaire containing all the variables of interest to attain the study objectives. The test statistics used to analyze the data were descriptive statistics and Chi-square (c2) or Fishers Exact Probability Test. Results: A significantly higher frequency of cases (67.7%) were given pre-lacteal feed, predominantly honey and sugar-water compared to control group (41.5%) (p = 0.008). Nearly 100% of controls were given colostrums compared to 75% of the cases. About one-third (31.3%) of the cases was exclusively breast-fed in comparison to 58.5% of the control group (p = 0.003). Over onequarter (27.7%) of the control were breast-fed upto 6 months of age, as opposed to only 1.5% cases (p < 0.001). Duration of predominant breast feeding for more than 6 months of age was also significantly higher in control group than that in case group (p = 0.001). Breast milk substitutes demonstrate their significant presence in cases (38.5%) than that in controls (9%) (p = 0.003). Conclusion: The study showed that rejection of colostrums, practice of prelacteal feeding, delayed initiation of breast feeding, early cessation of exclusive breast feeding and use of formula milk all were significantly higher in the malnourished group of children than those in their normal counterpart. Chatt Maa Shi Hosp Med Coll J; Vol.14 (2); Jul 2015; Page 43-47